Análise integrada do uso e aptidão agrícola dos solos na Amazônia Legal visando o desenvolvimento sustentável - Plá, Ronaldo Godolphim (2011)
Encroachment of the agricultural frontier over the Brazilian Amazon (Amazônia Legal) forest and savanna (cerrado) areas generates an array of negative environmental impacts, such as deforestation and fires. The conflict between the pressing agricultural front, mainly represented by cattle and soya productions, and the preservation of such forest and cerrado areas, presents itself as a central theme in the debate over the sustainable development involving the studied area. This work presents an integrated analyses of the current land use and land cover dedicated to agriculture in one of the Amazonian micro-regions locally known as Microrregião Norte Araguaia, in the Midwestern Brazilian state of Mato Grosso. This study also includes other cartographic data sets that characterize such aspects as the related Legally Protected Areas and Priority Conservation Areas. The integrated analyses was done by way of geoprocessing techniques, with which the cartographic information data sets were crossed referenced in a georeferenced environment, i.e. spatially set and adjusted with a known coordinate system. The land use and land cover maps permit us to see changes related to the advancement of the agricultural frontier as well as to identify stands of the original vegetation. Thus, through an integrated analysis, this work offers a set of decisive factors to restrict the advance of the agricultural frontier and preserve the remaining tracts of original forest, within the Microrregião do Norte Araguaia. The main results identify potential areas of still standing patches of the original Amazon forest and cerrado vegetations to be conserved and that they make up a total of 4.1 million hectares of forests and cerrado land, within the agricultural expansion zone. Coincidently, more than half of these areas present poor or non-existing agriculturally apt soils. These cartographic products seek to spatially identify potential areas and establish the criteria for its occupation and use.